Functional characterisation of small signalling peptides and a receptor kinase involved in root architecture development in Arabidopsis and crop species - Czyzewicz, Nathan (2017)
Post-embryonic root development is a plastic process by which plants are able to interface with the rhizosphere in order to provide anchorage, and increase surface area available for acquisition of nutrients and water. While root growth is governed primarily by auxin/cytokinin interactions, roots are able to sense the presence of surrounding nutrient deposits and changes to environmental conditions – directing growth accordingly – due to the action of signalling cascades. This thesis presents data pertaining to the characterisation of two signalling elements involved in governing root architecture; the small signalling peptide CLAVATA/EMBRYO SURROUNDING REGION 26 (CLE26), and the receptor kinase ARABIDOPSIS CRINKLY 4 (ACR4). Initially, the origins and evolutionary history of root architecture are explored, and an overview of signalling elements involved in root architectural development is provided, before discussing the potential benefits that manipulation of signalling events may allow in targeted crop improvement. To provide background on peptide signalling, the physiological and biochemical effects of small signalling peptides are discussed in view of the current literature, demonstrating the diverse range of developmental processes which are known to be regulated by these ligands and their known receptors. Following this, functional characterisation analyses indicate CLE26 as a novel, potent inhibitor of primary root growth and protophloem development in Arabidopsis, and is also shown to induce a similar effect upon exogenous application to several crop species. Furthermore, data is presented demonstrating the clear requirement for functional analysis during the development phase of creating antagonistic peptides, as a previously described antagonistic peptide technology was not applicable in all cases. Concluding the exploration of CLE26 signalling, a phosphoproteomics screen was conducted to probe further into CLE26 function, determining 23 putative effectors of CLE26 signalling, which are discussed in view of their potential to mediate CLE26 signalling, according to current literature. Next, the known roles of ACR4 and its orthologues are reviewed, demonstrating the importance of ACR4 signalling in many developmental processes, including regulation of asymmetric cell division during postembryonic root development. Although ACR4 activity is known to regulate asymmetric cell division in both columella stem cells and lateral root primordia, little is known about the downstream mediators of ACR4 signalling. In an attempt to fill this gap in knowledge, yeast 2-hybrid and co-immunoprecipitation approaches were employed. These two parallel proteomics screens together resulted in identification of 19 putative interactors of ACR4 signalling (PAIPs), which are discussed as potential mediators of ACR4 signalling in view of current literature. Of the identified PAIPs, three were further characterised by loss of function analysis, demonstrating that loss of PHOSPHOLIPASE Iγ2 and a PROTEIN OF UNKNOWN FUNCTION (At1g49840/UNK) was able to affect root architecture. Further in-silico characterisation of UNK reveals its similarity to soluble phospholipase receptors, which, alongside PLA-Iγ2, may potentially implicate ACR4 as a key player in a novel mechanism involved in regulation of bioactive lipid production.